The Efficacy of Cognitive-Behavioral Group Therapy on Symptoms of Attention-Deficit/ Hyperactivity Disorder and Executive Functions in Students with ADHD - Mahboubeh Moradi Siah Afshadi; Shole Amiri; Hooshang Talebi (پژوهش‌های کاربردی روانشناختی)
This study aimed to investigate the effectiveness of group cognitive behavioral therapy on the symptoms of Attention Deficit/Hyperactivity Disorder and the Executive Functions in university students with ADHD. The method was semi-experimental, involving a control group, a pre-test, a post-test, and a one-month follow-up. The statistical population encompasses all students at universities in Isfahan in 2021 who exhibit symptoms of ADHD. Randomly assigned to experimental and control groups, ten males and ten females were selected following the screening. The following research tools were employed: the Barkley Adult ADHD Rating Scale (BAARS-IV), Barkley deficit in Executive Functions Scale (BDEFS), Autistic Spectrum Quotient (ASQ), Mood Disorder Questionnaire (MDQ), Minnesota Multiphasic Personality Inventory (MMPI), Cattell Culture Fair Intelligence Test (CCFIT), and Diagnostic Interview for ADHD (DIVA). The data were processed using repeated measures analysis of variance. The results indicated that group cognitive behavioral therapy significantly reduced the symptoms of all ADHD subscales, with the exception of hyperactivity, and all executive functions subscales. The results of the Bonferroni test indicated the effectiveness of the treatment in the post-test phase for all subscales (except hyperactivity) and the follow-up phase except attention deficit and hyperactivity. It could be concluded that the dimensions of ADHD variable except for hyperactivity and executive functions variable in students with ADHD show significant improvement under the influence of cognitive behavioral therapy. This treatment procedure can be employed by therapists to enhance the health and capabilities of students who are affected.